Adsorption of Bismarck Brown R Dyes Using Mesoporous Silica MCM-48 - Zakir, Muhammad; Nuraeni, Andi; Taba, Paulina; Wahab, Abdul Wahid; Dali, Seniwati; Kasim, Syaharuddin; Nafie, Nursiah La (Indonesian Journal of Chemical Research, 2022)
The adsorption of Bismarck Brown R (BBR) dye has been conducted using mesoporous silica (MCM-48). We synthesized the adsorbent using Ludox HS-40 as a silica source and surfactants of Cetyl Trimethylammonium Bromide (CTAB) and Triton X-100. The characterization of MCM-48 was performed using Fourier transform infrared (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Various contact times were used to study the adsorption kinetics, and concentrations were used to study the adsorption isotherm. The optimum contact time of Bismarck Brown R dye was 120 minutes, and the adsorption followed a pseudo-second-order model. Based on the equation Langmuir and Freundlich adsorption isotherms, the adsorption capacity values of each are obtained 158.7301 mg g-1 and 4.3601 mg g-1. Our results showed that the material can be used as a new dye adsorbent.